Thai EFL Students' Responses to Teacher's Scaffolding Using Bamboozle in English Speaking Activities: A Case Study - Maulana, Nanda Putri; Kharisma, Adib Jasni (Pusdikra Publishing, 2026)
This study explores Thai EFL students' responses to teacher scaffolding implemented through Bamboozle-based speaking activities. Speaking remains one of the most challenging skills for EFL learners in Thailand due to limited exposure to English, high speaking anxiety, and teacher-centered instructional practices. To address these issues, teachers increasingly integrate gamified platforms with instructional scaffolding to support students' oral participation. This research employed a mixed-method case study design involving 22 Grade 8 students at a junior high school in Satun, Thailand. Data were collected through classroom observations, semi-structured interviews, questionnaires, and documentation. The findings reveal that teacher scaffolding during Bamboozle activities elicited positive linguistic, cognitive, and affective student responses. Linguistically, students demonstrated increased verbal participation, modified output, and self-repair. Cognitively, scaffolding helped students understand task demands and generate ideas more effectively. Affectively, students showed increased confidence, reduced anxiety, and greater willingness to communicate in English. The integration of instructional scaffolding with gamified speaking activities created a supportive learning environment that encouraged active participation and meaningful oral interaction. These findings provide practical implications for EFL teachers, suggesting that combining scaffolding strategies with game-based platforms such as Bamboozle can be an effective pedagogical approach to enhance students' speaking engagement and performance in secondary school contexts.